Neural mechanisms of attentional control differentiate trait and state negative affect - Laura D. Crocker; Wendy eHeller; Jeffrey M. Spielberg; Jeffrey M. Spielberg; Stacie L. Warren; Keith eBredemeier; Bradley P. Sutton; Marie T. Banich; Gregory A. Miller; Gregory A. Miller (Frontiers in Psychology, 2012)
The present research examined the hypothesis that cognitive processes are modulated differentially by trait and state negative affect (NA). Brain activation associated with trait and state NA was measured by fMRI during an attentional control task, the emotion-word Stroop. Performance on the task was disrupted only by state NA. Trait NA was associated with reduced activity in several regions, including a prefrontal area that has been shown to be involved in top-down, goal-directed attentional control. In contrast, state NA was associated with increased activity in several regions, including a prefrontal region that has been shown to be involved in stimulus-driven aspects of attentional control. Results suggest that NA has a significant impact on cognition, and that state and trait NA disrupt attentional control in distinct ways.